2019
DOI: 10.1167/iovs.18-26094
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Traumatic Optic Neuropathy in Mild Chronic Traumatic Brain Injury

Abstract: PURPOSE. To analyze the clinical presentation and optical coherence tomography (OCT) findings in indirect traumatic optic neuropathy (ITON) in veterans with chronic mild traumatic brain injury (mTBI). METHODS. This retrospective study is the first to describe the OCT pattern of subclinical to mild ITON in veterans with chronic mTBI. The thicknesses of the macular ganglion cell layer (mGCL), peripapillary retinal nerve fiber layer (pRNFL), and subfoveal choroidal layer were analyzed in young veterans who had mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Further, many symptoms may not be identified immediately, which can lead to missed diagnosis, especially in connection to the head injury. [2] Visual sequelae of TBI can also cause significant issues with recovery, [3] and can impact functional outcomes in children after even mild injuries. [4] Among the pathophysiologic mechanisms of TBI-associated visual deficits is traumatic optic neuropathy (TON).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, many symptoms may not be identified immediately, which can lead to missed diagnosis, especially in connection to the head injury. [2] Visual sequelae of TBI can also cause significant issues with recovery, [3] and can impact functional outcomes in children after even mild injuries. [4] Among the pathophysiologic mechanisms of TBI-associated visual deficits is traumatic optic neuropathy (TON).…”
Section: Introductionmentioning
confidence: 99%
“…[8] Optical coherence tomography (OCT) can also be a useful tool as it has revealed that indirect TON (iTON) results in significant thinning and deterioration of retinal layers at the time of injury and up to 35 years later, with retinal ganglion cell (RGC) death seemingly initiating subsequent deterioration of the other retinal layers. [2] Imaging of iTON within the brains of living human subjects, on the other hand, has only been possible through diffusion tensor imaging (DTI), thus limiting our knowledge of iTON. DTI has suggested that mild TBI can produce axonal injury in optic radiations [8][9][10] and the anterior thalamic radiations from the lateral geniculate body [9].…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al analyzed 19 veterans who suffered from indirect TON in mild chronic traumatic brain injury. [ 10 ] They found 3 major patterns of optical coherence tomography changes in these patients:…”
Section: Discussionmentioning
confidence: 99%
“…Mild traumatic brain injury is defined as traumatic head injury with conscious loss less than 30 minutes, a Glasgow coma scale score of 13 or more, and amnesia less than 24 hours. [ 10 ] In some uncomplicated brain concussion cases, computed tomography scans or MRI may not detect brain structural damage. However, clinicians should keep in mind that limited structural axonal injury and permanent loss of axonal function might be present without radio-image evidence.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The association of OCT measures of retinal layer thinning with the degree of central nervous system (CNS) neurodegeneration has been well-established in disorders such as Alzheimer disease, Parkinson disease, and multiple sclerosis. [13][14][15][16][17][18][19][20] OCT has been used to detect neurodegeneration in preclinical models of TBI [21][22][23] and in a few human studies, [24][25][26][27][28] but longitudinal studies have been lacking. The current study aimed to identify evidence of neurodegeneration through longitudinal evaluation of structural and functional changes in the visual nervous system and CNS in veterans with a history of mild TBI.…”
Section: Introductionmentioning
confidence: 99%